2008
DOI: 10.1016/j.pain.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Lack of TRPV1 inhibits cystitis-induced increased mechanical sensitivity in mice

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is highly expressed in primary afferent neurons. Tissue damage generates an array of chemical mediators that activate and sensitize afferent nerve fibers, and sensitization of afferent nerve fibers plays an important role in development of visceral pain. We investigated participation of TRPV1 in visceral pain associated with bladder inflammation induced in mice by systemic treatment with cyclophosphamide or intravesical instillation of acrolein. The effects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 39 publications
8
88
0
Order By: Relevance
“…Under a bright-field microscope, signs of edema, inflammatory infiltration, and hemorrhage were assessed in 6 -12 sections of both organs. Scoring was as previously described (60): 0 ϭ no edema; 1 ϭ edema limited to the submucosa, the width of which did not exceed the width of the detrusor; 2 ϭ edema present in the bladder wall but not the detrusor and the width of the submucosal region greater than, but less than twice than, the width of the detrusor; and 3 ϭ edema present in the bladder wall, possibly including occasional areas of the detrusor, and the width of the submucosal region greater than twice the width of the detrusor. Intermediate scores (0.5 points) were allowed whenever edema was focalized rather than generalized.…”
Section: Methodsmentioning
confidence: 99%
“…Under a bright-field microscope, signs of edema, inflammatory infiltration, and hemorrhage were assessed in 6 -12 sections of both organs. Scoring was as previously described (60): 0 ϭ no edema; 1 ϭ edema limited to the submucosa, the width of which did not exceed the width of the detrusor; 2 ϭ edema present in the bladder wall but not the detrusor and the width of the submucosal region greater than, but less than twice than, the width of the detrusor; and 3 ϭ edema present in the bladder wall, possibly including occasional areas of the detrusor, and the width of the submucosal region greater than twice the width of the detrusor. Intermediate scores (0.5 points) were allowed whenever edema was focalized rather than generalized.…”
Section: Methodsmentioning
confidence: 99%
“…For example, TRPV1-null animals show deficits in visceral mechanoreceptors, and their behavioral responses to colorectal distension are markedly reduced (Jones et al, 2005a). Of note, Trpv1(2/2) mice exhibit decreased mechanical hyper-reactivity of the bladder during cystitis (Wang et al, 2008c), implicating a role for TRPV1 in visceral pain associated with inflammatory disorders. Silencing by RNA interference of TRPV1 has been reported to ameliorate visceral pain in rats (Christoph et al, 2006).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…An interesting, alternative molecular pathway to increase TRPV1 activity during cystitis is by downregulation of TRPV1b, a TRPV1 splice variant that acts as a dominant negative modulator . In mice, genetic manipulation of the TRPV1 gene prevents spinal c-fos overexpression (a surrogate biochemical marker of nociceptive pain) and ameliorates mechanical hyperalgesia in experimental cystitis models (Wang et al, 2008c). Furthermore, the TRPV1 antagonist GRC-6211 (structure shown in Fig.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…In the pancreas, it is shown that TRPV1 is involved in the release of substance P (Nathan et al 2001). In the bladder, TRPV1 is an important target for the treatment of cystitis-induced bladder overactivity, but the exact localization is still under debate (De Ridder and Baert 2000; Charrua et al 2007;Wang et al 2008;Everaerts et al 2009). TRPV2 (ENSG00000187688; TRPV2) has 50% sequence identity to TRPV1 and is also expressed in DRG neurons, different brain regions, and non-neuronal tissues, including GI tract and smooth muscle cells ).…”
Section: Trpvsmentioning
confidence: 99%